1999
DOI: 10.1093/bja/82.6.941
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa surgery in the sitting position in a pregnant patient with cerebellopontine angle meningioma

Abstract: Primary brain tumours and pregnancy rarely occur together; meningioma and pregnancy is rarer still. We describe a 30-yr-old woman in the 25th week of pregnancy who underwent surgery in the sitting position for a large cerebellopontine angle meningioma that was compressing and displacing the pons and medulla. The surgical procedure and postoperative period were uneventful. This case demonstrates that when absolutely necessary, anaesthesia and neurosurgery for posterior fossa lesions can be successful during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…3 The signs and symptoms of a meningioma may initially appear during the second or third trimester of pregnancy and then subside in the postpartum period. As with this patient, the most frequent symptoms of a brain tumour such as headache, visual disturbance, nausea and vomiting are often attributed to pregnancy itself and hence the diagnosis may be delayed.…”
Section: Objectifmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The signs and symptoms of a meningioma may initially appear during the second or third trimester of pregnancy and then subside in the postpartum period. As with this patient, the most frequent symptoms of a brain tumour such as headache, visual disturbance, nausea and vomiting are often attributed to pregnancy itself and hence the diagnosis may be delayed.…”
Section: Objectifmentioning
confidence: 99%
“…The overall frequency of non-obstetric surgery during pregnancy is generally considered to be low and surgery for intracranial brain tumours is rare. [1][2][3][4][5] When urgent surgery is required there is controversy as to the role and need for intraoperative fetal heart rate (FHR) monitoring. We present the management of a pregnant patient for craniotomy without the use of FHR monitoring.…”
mentioning
confidence: 99%
“…When brain tumors are managed during pregnancy, certain factors must be taken into consideration, including the patient's physical condition; the gestational age; the site, size, and type of tumor; the neurological signs; and the patient's wishes [4]. Every attempt is usually made to bring the fetus to term.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the usual problems encountered in anaesthetizing pregnant patients, attention must be given to the prevention of elevations in intracranial pressure. Several authors have reported successful fetal outcomes after neurosurgery in such patients with the use of simple measures such as lidocaine and mannitol to control intracranial pressure accompanied by, when feasible, fetal echocardiographic monitoring [10,45].…”
Section: Complex Surgerymentioning
confidence: 99%